Disaggregation of the IT capital effects on firm performance: Empirical evidence from an IT asset portfolio perspective. Issue 4 (4th July 2018) - Kim, Tae Hun; Wimble, Matt; Sambamurthy, Vallabh
Abstract: Although prior research has frequently focused on aggregate IT capital, most firms invest in specific types with different goals. Each type of capital represents a distinct factor of a firm's production function. Drawing on a theory-of-production framework, we disaggregate overall IT capital into specific types to examine their unique effects on firm performance over time. We categorize these IT-specific production factors into a firm's installed personal computers for individual information access, servers for collective information access, storage capacity for information stock, and nodes for information flow . We investigate when and how each IT capital type contributes to firm performance by analyzing the 5-year panel data of 1, 548 US firms. Our findings show that individual information access capital and collective information access capital have immediate effects on profitability through cost efficiency or sales growth. By contrast, information stock capital has a lagged effect on profitability. In addition, information stock capital complements individual information access capital in improving profitability, as well as contributing to sales growth and cost efficiency equivalent to firm size. These results extend the existing research on firm-level effects of IT investments by demonstrating that different IT capital effects have unique ways of affecting firm performance.